2011
DOI: 10.18517/ijaseit.1.4.92
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Approach in Digital Circuit Design for 1-MHz Frequency PWM Gate Drive Application

Abstract: This paper discusses the design of a digital programmable logic circuit to produce a 5 V -output square wave pulses for four high power MOSFET switches using a fixed PWM circuit. It will be applied to drive the synchronous rectifier buck converter (SRBC) circuit. The PWM signals with multiple fixed time delay of 15 ns, 232 ns, 284 ns and 955 ns are generated. The steps taken to analyze each propagation time delay of each logic gate used and its combination are carefully studied. A multiplexer is added at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The considerable potential of the nitrides for high power, high frequency, and high temperature microelectronics (see e.g. [1]) has resulted in numerous studies of GaN and AlN layers grown onto both silicon and silicon carbide substrates. Both theoretical and experimental investigations have shown that the substrate plays a major role in determining the quality of the optoelectronic material deposited on it, and that the important feature inuencing this quality is the strain resulting from lattice--mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable potential of the nitrides for high power, high frequency, and high temperature microelectronics (see e.g. [1]) has resulted in numerous studies of GaN and AlN layers grown onto both silicon and silicon carbide substrates. Both theoretical and experimental investigations have shown that the substrate plays a major role in determining the quality of the optoelectronic material deposited on it, and that the important feature inuencing this quality is the strain resulting from lattice--mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…1 "Wide bandgap semiconductors" are a relatively new field of research in materials science, and most of interest in nitrides today orbits around optoelectronics, such as LEDs, lasers, and high-power/temperature/frequency electronics, with new commercial devices becoming available every day. [2][3][4][5][6][7][8] Regarding GaN and InN bandgaps, this large variation can be also considered initially promising to be applied in solar cell multijunctions technology, with a potential efficiency comparable to standard Ge/InGaAs/InGaP technology. 9 However, considering each subcell of a multijunction solar cell as composed with InGaN alloy materials with different In compositions (providing large variation in bandgap), the system shall present large mismatch in lattice parameters.…”
mentioning
confidence: 99%